Medial unstressed vowels in northwestern of Sao Paulo: the role of social variable on vowel raising - Pavezi, Vanessa Cristina; Tenani, Luciani; Goncalves, Sebastiao Carlos Leite (Letras de hoje, 2012)
In this paper, we investigate to which extent social variables act on the medial vowel raising phenomenon in the Portuguese variety spoken in Sao Jose do Rio Preto, a city in the countryside of Sao Paulo State. Based on the theoretical-methodological model of Sociolinguistics Variacionist, we analyse speech samples from this city, the Iboruna database. The results show that the vowel raising applies: (i) for both men and women; (ii) in all age groups and, (iii) in all levels of formal education. Taking into consideration the results of analysis of social and linguistic variables selected by the program GoldVarb, we find evidences that vowel raising phenomenon is not sensitive to social pressures in the speech community studied, which allows us to affirm that it is not a phenomenon socially stigmatized and the variation in its implementation is more strongly subject to linguistic variables. Adapted from the source document.